Analisis Deskriptif Program Edutainment For Your Pagi Di Trans7 Dalam Meningkatkan Literasi Digital Remaja - Ikhsanul Alhafizh; Fatma Sukmawati; Faris Farabi (Universitas Sebelas Maret, 2026)
This study aims to describe and analyze the strategic utilization of the For Your Pagi (FYP) edutainment program on Trans7 in improving teenager digital literacy. Employing a qualitative approach with a qualitative descriptive design, this research gathered data through a purposive sampling technique involving four primary informants: two internal media practitioners (the producer and creative team member of Trans7) and two external informants (teenagers aged 17–20). Data collection techniques were rigorously executed via semi-structured interviews, participatory observation during the researcher’s embedded internship, and documentation studies of broadcasting scripts and actual televised episodes. Data validity was ensured through source and technique triangulation, and analysis was systematically performed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the FYP program effectively deploys educational message design strategies within a non-formal broadcasting environment by systematically integrating John Keller’s ARCS Motivation Model (Attention, Relevance, Confidence, Satisfaction). This structural edutainment balance exhibits a verifiable impact on accelerating the digital literacy competencies of teenagers based on the four pillars of Paul Gilster’s Theory. However, a significant operational constraint persists.